(untitled) (Heritage, 2023)
In the paper, the authors dealt with the problems of the application of educational orders in the Republic of Serbia from a methodological and criminal law approach. Educational orders, as sui generis measures, can be applied both before the initiation of criminal proceedings and during the duration of the criminal proceedings, with the focus of this paper being on their application before the initiation of criminal proceedings. The legislative national framework of the Republic of Serbia regarding the application of educational orders is based on the Law on Juvenile Offenders and the Criminal Protection of Juveniles (ZM) from 2005, with the authors taking into account the changes mentioned in the Draft ZM. Two hypotheses are defined in the paper. The first hypothesis is that educational orders as diversionary models of treatment of juvenile offenders and non-penal measures are relatively recent in the Republic of Serbia. Therefore, the mentioned measures cannot be nor are they sufficiently developed, which leads to incomplete satisfaction of restorative justice towards minors and injured parties, when the law allows us to do so. The second hypothesis is that organizational factors are of special importance for the success of the implementation of educational orders. In the paper, the authors point out that the new proposal of the Law on Juvenile Offenders and Criminal Protection of Minors enriches the system of educational orders and significantly expands the scope of their application. A certain significant rate of recidivism could be avoided by the combined and balanced application of repressive measures and educational orders as a sui generis measure. The paper gives de lege ferenda recommendations in the direction of simplifying the procedure that follows the beginning of the application of educational orders from the time when a criminal offense is committed, with the fact that the types of educational orders must necessarily follow the state and trend of juvenile crime.